Penerapan Metode Regresi Linear Berganda Dalam Prediksi Produksi Barang Pada PT. Depot Kayu Saudara - Erjisun, Erjisun; Siswanto, Siswanto; Kanedi, Indra (UNIVED Press, 2024)
PT. Brother Wood Depot is a furniture company that produces furniture and other items. Along with changes in goods production at PT. Brother Wood Depot from year to year, so it is necessary to estimate in the future whether production of goods will decrease or increase. Sometimes when we assume that the amount of production in the following month will decrease and reduce the amount of production, it turns out that demand in the following month actually increases. Application of the Multiple Linear Regression Method in predicting goods production at PT. The Brother Wood Depot is used to help provide an estimate of the amount of goods production that should be based on prediction results using the Multiple Linear Regression Method from aspects of supply and demand for goods. In determining the predicted results for the amount of goods produced in the following month and year, there are 3 supporting variables used which are used as time series data (past data), namely inventory, demand and production of goods in the previous month and year. Based on testing of the goods production prediction application at PT. It was found that the functionality of the application runs as expected, and is able to display predicted results of goods production for the next month and year using the Multiple Linear Regression Method